Features of Mechanisms of Socialization and Resocialization of Minors from the Point of View of Increasing their Efficiency - Dubovyk, Kateryna (Theory and Practice of Public Administration, 2024)
In order to improve the mechanisms of socialization and resocialization of minors and to establish control over such negative phenomena in the economic, social and spiritual spheres as social maladaptation, decline of spirituality, devaluation of moral values, which significantly affect the content and nature of social relations, significant changes are proposed to the Regulations on Services in the affairs of minors and special institutions for them, expansion of their powers, definition of tasks and rights. It is noted that modern institutions of socialization do not fully satisfy society’s need for the formation of valuable qualities, socially approved behavioral norms, worldview beliefs and life positions in adolescents, which causes the spread of offenses by minors. Attention is drawn to the fact that in Ukraine there is a lack of a perfect system of resocialization of minors, as a result of which minor offenders remain in the same environment in which they were and were brought up before, social factors put pressure on them, without taking into account what their further education is impossible. It was noted that for the full-fledged resocialization of offenders, an appropriate state management policy is necessary, which would ensure effective coordination of the activities of services for children, pedagogical and labor teams, family, and the environment. Only on the basis of combining their efforts, establishing a productive interaction, can you count on the success of the education process. It is indicated that all this requires the introduction of new mechanisms of state management of social policy, coordination of the actions of state administration bodies and local self-government bodies, civil society institutions regarding the resocialization of minors with deviant behavior. The powers of children’s services were analyzed. It is pointed out that the list of powers does not mention anything about the coordination of children’s services with the centers of social services for family and youth. It is proposed to supplement the powers of children’s affairs services with the following: analysis of the state of affairs and the causes of deviant behavior among minors in the process of implementing state policy in the field of children’s rights protection; developing proposals for defining general approaches to scientific and methodological support The powers of children’s services were analyzed. It is pointed out that the list of powers does not mention anything about the coordination of children’s services with the centers of social services for family and youth. It is proposed to supplement the powers of children’s affairs services with the following: analysis of the state of affairs and the causes of deviant behavior among minors in the process of implementing state policy in the field of children’s rights protection; developing proposals for defining general approaches to scientific and methodological support.